2020
DOI: 10.1111/sjpe.12240
|View full text |Cite
|
Sign up to set email alerts
|

The impact of product subsidies on plant‐level total factor productivity in Britain, 1997–2014

Abstract: The United Kingdom's imminent departure from the European Union provides the opportunity for a more selective industrial strategy. This paper therefore analyses the effect of product subsidies on productivity in British manufacturing plants between 1997 and 2014 in order to provide evidence on the desirability of extending their use. The results suggest that low rates of subsidisation had either a positive or no effect but higher rates had a negative effect on total factor productivity in some sectors. This im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The entrepreneurship and SME policies aiming to stimulate Czech entrepreneurial activity (and productivity of the Czech firms) may be targeted at the soft policy actions, including advisory services and counselling on business development or risk management (Hoogendoorn et al, 2019) and on the provision of financial capital allowing firms to strive for the more challenging and growth-oriented projects with the help of public aid (Dvoulet y et al, 2020). Furthermore, TFP should be used as an outcome indicator in evaluation studies, informing policymakers whether the policy action delivered the expected change in the firm productivity, as noted recently by Dvoulet y et al (2021) or Harris and Moffat (2020). We also note that the Czech policymakers should become interested in the characteristics of unproductive firms and zombie companies (which are over-indebted or even without equity) through the adjustment of the appropriate bankruptcy rules and more frequent (and carefully targeted) checks of firm accounting, which may result in the elimination of these companies from the market and consequent in reallocations of resources towards the better alternative usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entrepreneurship and SME policies aiming to stimulate Czech entrepreneurial activity (and productivity of the Czech firms) may be targeted at the soft policy actions, including advisory services and counselling on business development or risk management (Hoogendoorn et al, 2019) and on the provision of financial capital allowing firms to strive for the more challenging and growth-oriented projects with the help of public aid (Dvoulet y et al, 2020). Furthermore, TFP should be used as an outcome indicator in evaluation studies, informing policymakers whether the policy action delivered the expected change in the firm productivity, as noted recently by Dvoulet y et al (2021) or Harris and Moffat (2020). We also note that the Czech policymakers should become interested in the characteristics of unproductive firms and zombie companies (which are over-indebted or even without equity) through the adjustment of the appropriate bankruptcy rules and more frequent (and carefully targeted) checks of firm accounting, which may result in the elimination of these companies from the market and consequent in reallocations of resources towards the better alternative usage.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on productivity have also highlighted the role of spatial variation (Cie slik et al, 2019;Giannakis and Bruggeman, 2015;Haldane, 2017;Mart ınez-Victoria et al, 2018). It is widely acknowledged that firms are dependent on external influences for their functioning (Henley, 2018) and are influenced by spatially differentiating factors, such as geographical opportunities and constraints, resources, spillover factors (Carlsson and Dahlberg, 2003) and public policy (Dvoulet y et al, 2020(Dvoulet y et al, , 2021Harris and Moffat, 2020;Pickernell et al, 2013). The interconnection between these factors has been described recently in the theory of entrepreneurship/entrepreneurial ecosystem (Stam, 2015), describing the surroundings of entrepreneurial activity and its role in the growth of a particular business.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The estimates used to construct the policy rule instrument are presented in columns 1 and 2 of Table 3. 19 As discussed in Section III, these results are from ordered probit estimates of the area support levels (NGE). Note that three of the variables used as indicators in 2000 by policymakers were not used in 1993 (the employment rate, the ILO unemployment rate, and the share of manufacturing workers), so we drop these variables from the regressions in column 1, i.e., setting the coefficients on these variables to be 0.…”
Section: Estimating the Policy Rulesmentioning
confidence: 99%
“…Looking across Table 3, the signs are generally intuitive. Areas with higher GDP per capita, higher population density, more skilled workers, higher business start-up rates, lower structural unemployment rates, higher activity rates, and higher 19 Online Appendix Table A2 has definitions and descriptive statistics. Note: TFP is computed using a Solow residual "factor share" method and relative to an industry × year average (see online Appendix C).…”
Section: Estimating the Policy Rulesmentioning
confidence: 99%
“…Several studies have theoretically and empirically identified factors that determine TFP (see Silveira et al 2021 for a review of literature of TFP determinants). Theory suggests that human capital (ibid; Arazmuradov et al 2014;Danska-Borsiak 2018;Akinlo and Adejumo 2016), trade (Bhattacharya et al 2021;Kim 2016), FDI/imports (Bhattacharya et al 2021;Kim 2016;Akinlo and Adejumo 2016;Harris and Moffat 2020), and R&D expenses (Danska-Borsiak 2018;Otsuka 2017;Kim 2016) are the main determinants of TFP growth. However, it is recognized that the latter is the main driver of TFP growth (among others, Saleem et al 2019;Huang et al 2019;Shabbir and Yaqoob 2019;Sharif et al 2021;Pegkas et al 2020;Tsamadias et al 2019;Haider et al 2019;Griliches 1979Griliches , 1994Griffith et al 2004;Edquist and Henrekson 2006;Hall et al 2009;Eberhardt et al 2013;Donghyun et al 2014;Gehringeer et al 2015;Venturini 2015) because it facilitates the adoption and implementation of new technologies exogenously facilitating the domestic production of technological innovations.…”
Section: The Fie Approach To Measuring Tfp Changementioning
confidence: 99%